No Chance of Success. State Agrarian Real Estate 1946–1949. A Contribution to the Research on the History of the State Agricultural Sector in Poland - Machałek, Małgorzata (Studia Historiae Oeconomicae, 2021)
The years of activity of the PNZ (Państwowe Nieruchomości Ziemskie – State Agrarian Real Estate) fell into the period of post-war agricultural reconstruction and management of Recovered Territories. Initially, their main task was to prepare for the parceling out of large landed estates, which was important for the settlement campaign. The target task was to run specialized farms that would supply the entire agriculture with seed and breeding material. After the escape of S. Mikołajczyk, the communists changed the priorities of PNZ activity, which from then on were to deal with large-scale production, and above all, manage about 1,200 hectares of agricultural land. The vast majority of the area used by PNZ was located in the western and northern regions of the country. The best conditions existed in those areas for establishing a state sector in agriculture. In spite of many achievements, PNZ was liquidated because the communists wanted to get rid of the prewar staff of specialists, mostly landowners, from the enterprise. This decision was political in nature. State farms were then created to replace PNZ.